Peranan BAZNAS Dan Sistem Pengelolaan Dana Zakat Terhadap Kelompok Bina Zakat (KBZ) Di Kabupaten Oku Timur - Muhamad Diem, Abu Bakar Mail Batin (UIN Sunan Kudus, 2018)
Economic problems are a fundamental problem that occurs in every region and is experienced by all people. This problem occurs because of the gap between the rich and the poor, giving rise to the symptoms of poverty, with the emergence of poverty the National Amil Zakat Agency (BAZNAS) becomes one of the government-owned virtue institutions which aims to collect and channel zakat funds. In its distribution, BAZNAS formed the Bina Zakat Group (KBZ) spread in various regions, one of which was in East OKU Regency, precisely in the village of Banuayu and the village of Muncak Kabau. Each Bina Zakat Group (KBZ) received Rp.10,000,000 each as a stimulant fund.In the discussion concluded that, first the role of BAZNASdistribution has not gone well, this was due to a lack of supervision and assistance for the development of businesses run by the community using productive zakat funds, both KBZ East OKU who received capital assistance, only KBZ in Banuayu village succeeded in running a brick business where it had funds of Rp.32,000,000 and is still running today; Whereas KBZ in Muncak Kabau village failed to develop zakat funds because the type of goat livestock business was not suitable because livestock which had originally grown from 10 to 17, now died. The missing funds have no demands to replace them. Then the two systems return to the religious factors of the community.